Adaptive Aspects of the Social Situation of the Development of Adolescents in the Conditions of Teaching in the Organization of Secondary Vocational Education - Myskin S.V; Makeeva G. A (Moscow State University of Psychology and Education, 2021)
The study aims at theoretical analysis and empirical identification of adaptive aspects of the social situation of adolescents' development to the new learning conditions. The article presents the materials of the first stage of the empirical study obtained on a sample of 1st-year students of the Moscow organization of secondary vocational education. The study involved 500 respondents aged 16 to 17 years, of which 92% were female. The study included measurements on 7 scales for 5-7 days. We used a projective closed method for assessing the formation of the components of educational activity (it includes two options: for boys and girls). The obtained data suggest that the natural process of adaptation of adolescents to the new conditions of college education is based on its complementary components. At the same time, entering a new situation of social development is accompanied by the emergence of a number of contradictions between the actual needs of a young person and the conditions for their satisfaction. The need to form a system of interpersonal relationships with both peers and significant adults (teachers) actualizes the need for self-affirmation, which is characteristic of the younger adolescence, the previous stage of personal development. The revealed contradiction leads to the formation of an uncertain professional picture of the world.